THE EFFECTS OF ORGANIC ACIDS ON THE DISSOLUTION OF SILICATE MINERALS: A CASE STUDY OF OXALATE CATALYSIS OF KAOLINITE DISSOLUTION - Cama J.; Ganor J. (My University, 2006)
Most studies agree that the dissolution rate of aluminosilicates in the presence of oxalic and other simple carboxylic acids is faster than the rate with non-organic acid under the same pH. However, the mechanisms by which organic ligands enhance the dissolution of minerals are in debate. The main goal of this paper was to study the mechanism that controls the dissolution rate of kaolinite in the presence of oxalate under far from equilibrium conditions (-29 < ?Gr < -18 kcal mol-1). Two types of experiments were performed: non-stirred flow-through dissolution experiments and batch type adsorption isotherms. All the experiments were conducted at pH 2.5-3.5 in a thermostatic water-bath held at a constant temperature of 25.0, 50.0 or 70.0 ? 0.1 °C. Kaolinite dissolution rates were obtained based on the release of silicon and aluminum at steady state. The results show good agreement between these two estimates of kaolinite dissolution rate. At constant temperature, there is a general trend of increase in the overall dissolution rate as a function of the total concentration of oxalate in solution. The overall kaolinite dissolution rates in the presence of oxalate was up to 30 times faster than the dissolution rate of kaolinite at the same temperature and pH without oxalate as was observed in our previous study. Therefore, these rate differences are related to differences in oxalate and aluminum concentrations. Within the experimental variability, the oxalate adsorption at 25, 50, and 70 °C showed the same dependence on the sum of the activities of oxalate and bioxalate in solution. The change of oxalate concentration on the kaolinite surface (Cs,ox) as a function of the sum of the activities of the oxalate and bioxalate in solution may be described by the general adsorption isotherm:{A formula is presented}The possible effect of oxalate on the proton-promoted dissolution rate was examined by comparing the results of the present study to literature observations on the effects on kaolinite dissolution rate of deviation from equilibrium and Al inhibition, respectively. The comparison indicates that the effect of oxalate on kaolinite dissolution rate is not related to Al inhibition or saturation state. Therefore, we suggest that oxalate catalyzes kaolinite dissolution through an oxalate-specific mechanism. The oxalate-promoted dissolution is best described using a quadratic rate law, i.e., a rate law in which the oxalate-promoted dissolution rate depends on the square of the oxalate surface concentration. A quadratic rate law may represent a mechanism in which the dissolution is catalyzed by the simultaneous adsorption of two ligands on two neighboring edge aluminol sites. This mechanism is supported by the observation that on saturation, the amount of adsorbed oxalate is similar to the amount of available Al surface sites on the kaolinite edge, and is much smaller than the amount of available Al surface sites on the basal planes. This observation indicates that the adsorption of oxalate occurs mainly on edge aluminol sites, and suggests that the formation of Al-oxalate complexes on two neighboring edge aluminol sites must be reasonably common above a threshold oxalate concentration. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ALUMINOSILICATE; CARBOXYLIC ACID; CATALYSIS; DISSOLUTION; KAOLINITE; OXALATE